IMPERATIVENESS AND SPEECH ECONOMY IN MESSENGER INSTRUCTIONS - Khasanova Dilnoza Tojidinovna (International Journal of Literature and Language Studies, 2026)
This research paper analyzes the specific linguopragmatic features of instructional discourse in digital communication, in particular in messengers. The article highlights the hybrid form of instructions in messenger communication, which, unlike traditional written texts, combines the brevity, situationality, and dialogic nature of oral speech. The results show that digital instructional discourse serves to organize communication quickly and effectively, based on the principle of